2021
DOI: 10.1590/1413-785220212906242008
|View full text |Cite
|
Sign up to set email alerts
|

Intraarticular Epsilon Aminocaproic Acid Versus Tranexamic Acid in Total Knee Arthroplasty

Abstract: Objective: To examine and compare the clinical efficacy of intraarticular epsilon aminocaproic acid (EACA) and tranexamic acid (TXA) in total knee arthroplasty (TKA). Methods: This study was a prospective, single-center, double-blinded randomized controlled trial, including sixty patients with osteoarthritis of the knee divided into two groups of 30 patients. In the TXA group, 1 g of TXA (0.05 g/ml) was applied intraarticularly, and in the EACA group, 4 g of EACA (0.2 g/ml) was applied intraarticularly. Ser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 13 publications
0
7
0
1
Order By: Relevance
“…A total of 38 12,24–60 studies, which consisted of 29 RCTs and 9 non‐RCTs, were included in the network analysis. Based on previously described research strategy, we identified 5403 studies.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A total of 38 12,24–60 studies, which consisted of 29 RCTs and 9 non‐RCTs, were included in the network analysis. Based on previously described research strategy, we identified 5403 studies.…”
Section: Resultsmentioning
confidence: 99%
“…Twenty-nine studies 12,24,25,[29][30][31][32][33]36,37,[39][40][41][42][43][44][45]47,[49][50][51][52][53][54][55][56][57][58][59] reported PE/DVT rates. Network diagrams of comparisons on PE/DVT rates are shown in Fig.…”
Section: Pe/dvt Ratesmentioning
confidence: 99%
“…A última questão a todos foi se o paciente teria disposição para se internar para a cirurgia eletiva naquele momento. Ainda aplicamos o questionário WOMAC 9 para comparação com pacientes desse mesmo hospital que responderam esse mesmo questionário dois anos antes da pandemia (entre julho e dezembro de 2017) 10 .…”
Section: Materiais E Métodosunclassified
“…Antifibrinolytic agents could be administrated intravenously, intra‐articularly, orally or combined. Though several studies have compared the efficacy of TXA and EACA in total joint replacement surgery, none of them compared the two drugs when the drugs were administered in an intravenous and intra‐articular (IV/IA) combined fashion 20–22 . IV/IA combined administration has become more and more common recently in TKA as it can reduce both apparent and hidden blood loss 23,24 .…”
Section: Introductionmentioning
confidence: 99%
“…Though several studies have compared the efficacy of TXA and EACA in total joint replacement surgery, none of them compared the two drugs when the drugs were administered in an intravenous and intra‐articular (IV/IA) combined fashion. 20 , 21 , 22 IV/IA combined administration has become more and more common recently in TKA as it can reduce both apparent and hidden blood loss. 23 , 24 However, the optimal regimen of antifibrinolytic agents, as well as efficacy of EACA and TXA, are still controversial in TKA.…”
Section: Introductionmentioning
confidence: 99%